Expression of CPAF, IFN-γ and IL-10 in different genotypes of Chlamydia trachomatis isolated from mice genital infection - Liu-yuan WANG; Pei-zhen ZHAO; Yao-hua XUE; Li-gang YANG; He-ping ZHENG; Bin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To analyze differences in expressions of CPAF, IFN-γ and IL-10 by establishing mouse genital tract infection with different CT genotypes. Methods: Seventy female Balb/c mice were randomly divided into E group, F group, J group, K group, H group, blank control group and experimental control group. Chlamydia trachomatis genotypes E, F, J, K and H (30 μL) were inoculated into vagina respectively. The blank control group was not treated, while the experimental control group was inoculated into vagina with 30 μL SPG. Expression of CPAF, IFN-γ and IL-10 in the uterus and fallopian tube was detected by ELISA on day 35 post-inoculation. Results: On day 35 post-inoculation, the concentration of CPAF in homogenate of uterus and fallopian tube in group H was significantly higher than that in group E, F and J (all P<0.05). The concentration of CPAF in group K was significantly higher than that in group F (P<0.05). The concentration of IFN-γ and IL-10 in uterus and fallopian tube homogenate in group H and K were significantly higher than that in group E, F and J (all P<0.05). Conclusion: The expression of CPAF, IFN-γ and IL-10 in the upper genital tract of mice infected with different types of CT show differences significantly, indicating that different genotypes of CT may cause different clinical outcomes.